Talent Management System : Challenges For Organizational Sustainability - Anjar Sulistyorini (Syntax Corporation, 2023)
Business developments that are increasingly competitive and full of challenges and even uncertainty require organizations to adapt to changes for sustainability. Talent management is a series of organizational activities in attracting, retaining and developing talented people needed by the organization.This study presents the main concepts in the talent management system and the success factors for implementing a talent management system in organizations through a comprehensive and relevant literature review. The results of this study are expected to be considered by organizations in managing talent effectively.